Analisis Faktor Yang Mempengaruhi Permintaan Agregat Di SUmatera Barat (JURNAL ECONOMICA : Research of Economic And Economic Education, 2017)
The purpose of this research are to know and analysis influence inflation,  the money supply, interest rates , government spending , consumption and exchange rate on aggregate demand in West Sumatra . The form of time series data from the first quarter of 2000 - the fourth quarter of 2010. This study uses a double linear regression  model analysis tool with the Ordinary Least Square method ( OLS ). The results showed that inflation , money supply , interest rates , government spending and consumption have a significant effect on aggregate demand in West Sumatra.